Mettre en contact plutôt que mettre à distance le monde sensible. Pour une épistémologie écoféministe du toucher - Anna Berrard; Anaïs Choulet-Vallet (Tracés, 2022)
In this article, we brought together our researches on the sense of touch and ecofeminism to introduce a new epistemological approach to this sense. We study the consequences of the politics of distancing on sensitive experiences and the possibilities of reclaiming contact through touch. Using an ecofeminist and a critical visiocentric conceptual grid, we question how “distancing” structures our scientific paradigms, social representations and, therefore, our actions. Through the extended example of endometriosis and care practices, we discuss the paradoxes of sensitive experience in a production-driven and patriarchal context through the development of concepts such as “sensitive work” and “touch without contact”. Eventually, we underline the epistemological and radical political possibilities of an ecofeminist sense of touch which could, on the one hand, multiply epistemic agents and, on the other hand, introduce renewed and alternatives understandings of the social world.